INCLUSIONARY HOUSING IN INDONESIA: THE ROLE OF BALANCED RESIDENTIAL RATIO 1:3:6 IN MAKASSAR - , Vera Yuniati, Prof. Ir. Bakti Setiawan, MA., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This research attempts to find out how inclusionary housing is implemented in Indonesia through the balanced residential ratio 1:3:6 regulation (Lingkungan Hunian Berimbang â LHB). The regulation was introduced by the national government in 1992 for implementation at local level by all municipalities and regencies. There are two main objectives of the LHB 1:3:6 regulation: (1) to produce affordable housing, and (2) to encourage more socially integrated development via mixed-income residential areas and cross-subsidies. Henceforth, every new residential development by a private developer should reflect the 1:3:6 ratio (1 high-income, 3 middle-income and 6 low-income units). Using the case of Makassar City, the capital city of South Sulawesi Province and the largest city in the eastern part of Indonesia, the author tries to assess the implementation of the balanced residential ratio 1:3:6 regulation from four dimensions - legal, economic, financial, and social - during period 1993 â 2003. Those dimensions are discussed in the context of provision for affordable housing through the application of land value capture. Thus other issues such as long-term affordability and social ethnic integration are not covered in this research. The general finding for the balanced residential ratio, LHB 1:3:6, which was adopted by the Makassar Local Government in 1992, has been lack of implementation. The local government simply adopted it without formulating more detailed local regulations or adapting it to the cityâs ordinances. Although the procedures and sanctions are clearly stated, the absence of a dedicated institution or committee at national and local levels in coordinating, controlling, and monitoring the implementation of the regulation, results in non-compliance. The legal basis provided by the national government, which is at ministerial level, and the absence of specific local regulations, means that the sanctions stated in the balanced residential ratio regulation were not applied by the local government. On the other hand, the incentives in the form of fast-track permit and reduction of retribution for building permit provided by local governments are not enough to motivate developers. This is because developers usually look for the highest possible profit. However, it is economically feasible for developers to fulfill the inclusionary obligation. This is indicated by the relatively high increment of land value gained by developers compared to the value of the land at the time they purchased it. Factors that influenced that result are the chosen location at periphery areas and also in an adjacent municipality, as well as the initial land use which was vacant land. Meanwhile, economic impacts of the balanced residential ratio regulation on price and production of luxurious units were not clear because of lack of data and studies regarding those issues.In addition, during the period 1993 â 2003 housing production by developers in Makassar was dominated by the medium type which reached 54% of total housing production in that period. The rest of production was shared almost equally between the basic houses and luxurious houses. The data shows that the percentage was 24% for the former and 21% for the latter. However, from the total amount of basic houses built in Makassar, 55% were produced from projects that implemented 1:3:6 regulation. Concerning the extent that the balanced residential regulation addressed the spatial segregation issue, this research barely found housing development since 1993 that followed the requirement to build a mixed-residential development within one contiguous area. In the case of the selected project in Makassar, Bukit Baruga Residential, the developer built the basic houses in an adjacent municipality where the land price was very cheap. This indicates that spatial integration through mix-residential area is hard to achieve. Meanwhile, changing in policy has not given much significant improvements regarding spatial integration purpose. Similar with the former 1:3:6 regulation, the new balanced residential ratio introduced in 2011 still illustrates ambiguity. At one side it makes mix-residential in one contiguous area compulsory for large scale residential development. But on the other hand, the developing of basic houses is allowed at different area as long as the location is in the same municipality or regency. Although some disincentives are introduced, but spatial integration seems still negotiable. This ambiguity is contrary to the objective of the regulation itself that trying to develop spatially integrated communities by mixing different types of housing within one contiguous area. Finally, this research admits that this policy could play an important role for local governments to address issues of affordable housing and spatial integration. It enables local government to recapture the increment of land value obtained by private developers to provide affordable housing for low income households. Lessons learnt from the past suggest that clear and detailed regulations, as well as strong political will of the local government, are needed to be able to mobilize the increment on land value obtained by developers. Although it is economically feasible for developers to set aside a certain portion of housing units and make it affordable for low income households, it will not be recaptured if local government does not fully understand the opportunities that this regulation offers in assisting them with provision of affordable housing.